Myeloid Sarcoma of Temporal Bone: A Rare Manifestation of Relapse Acute Myeloid Leukemia - Goh, Bee See (Indian J Otolaryngol Head Neck Surg, 2015)
Myeloid sarcoma is a rare malignant extramedullary neoplasm of myeloid precursor cells. This disorder may occur in concomitance with or precede development of acute or chronic myeloid leukemia. Sometimes, it is the initial manifestation of relapse in a previously treated acute myeloid leukemia. We report a case of 11 years old boy with acute myeloid leukemia in remission state, presented with short history of right otalgia associated with facial nerve palsy. Diagnosis of right acute mastoiditis with facial nerve palsy as complication of acute otitis media was made initially. Patient underwent simple cortical mastoidectomy but histopathology from soft tissue that was sent revealed diagnosis of myeloid sarcoma. A leukemic relapse was confirmed by paediatric oncologist through bone marrow biopsy. Chemotherapy was commenced but patient responded poorly to the treatment.